Problem Based Learning Model with Experiential Learning to Increase Creative Thinking and Critical Thinking Ability - Dianita, Beti; Vinta Angela Tiarani (LPPM Undiksha, 2023)
The problem of students' creative thinking and critical thinking skills in science learning still needs to improve, and more teachers must apply innovative learning models. This study aimed to analyze the effect of the problem-based learning model assisted by experiential learning in developing students' 21st-century thinking skills, namely creative thinking and critical thinking in science learning. This type of research is qualitative. The research method used in this research is quantitative, namely quasi-experimental. There are two research samples experimental class and the control class. Data collection methods are done through interviews, observations, tests and documentation. The analysis technique used is a normality test, homogeneity, T-test, and multivariate test with MANOVA. The results showed a significant increase in the posttest results of student's creative thinking and critical thinking skills after applying the problem-based learning model assisted by experiential learning. The MANOVA test results show that learning in the experimental and control classes increases in value even though the average differs. It was concluded that the problem-based learning model assisted by experiential learning could improve students' 21st-century thinking skills, namely creative thinking and critical thinking in science learning.